Underwater Archaeology of a Pacific Battlefield The WWII Battle of Saipan - McKinnon, Jennifer F.; Carrell, Toni L. (SpringerBriefs in Underwater Archaeology, 2015)
Battlefields have been the object of fascination for millions of tourists and the subjects of elaborate interpretation projects. This volume will outline the process and results of developing the WWII Maritime Heritage Trail: Battle of Saipan Project. This book will provide examples of how a group of archaeologists, managers and a community took a specific battle and transformed it from a collection of unknown archaeological sites into a comprehensive storied battlescape that reflects the individuals and actions of those who were involved. It will provide an in-depth view of current maritime archaeological research on submerged battlefield sites, the development of a WWII battlefield maritime heritage trail, as well as the problems and solutions of such an effort. It will cover subjects such as: -heritage and dark tourism-conflict or battlefield archaeology-public interpretation, and community engagement. This volume will serve as a practical review of a project influenced by a range of complementary areas of study and inclusive of many stakeholders, from the public to the professional and beyond. It provides an example of a balanced approach towards research and interpreting archaeological sites through the identification and inclusion of the various stakeholders (professional and community) and an awareness of what was being included, ignored, or inadequately represented in the research and interpretation.